Evaluation of Different Vaireties of Onion and their Transplanting Times for Off-season Production in Mid Hills of Nepal - Gautam, IP; Khatri, B; Paudel, GP (Nepal Agriculture Research Journal, 2009)
A field experiment was conducted at the agro-ecological research site (AER site) of the RegionalAgriculture Regional Station, Lumle, at Deurali in Palpa (1200 masl) during rainy season of2004 and 2005. The main objective of the experiment was to evaluate the different varieties ofonion and their transplanting time for off-season production in mid hill conditions. Treatmentswere four onion varieties, namely LR-241, N-53, Nasik Red and Red Creole and four transplantingdates as 25 July, 5 August, 15 August, and 25 August. The trial was conducted in RCBD withfactorial arrangement of treatments and replicated three times considering farmer as a replication.The plot size was maintained 1.4 m2 (1.4 x 1 m2). Observation was recorded on plant height, plantstand at maturity, diameter and length of bulbs, neck thickness and yield of green bulbs and greentops. The varieties showed a significant different only on the fresh bulb production. Transplantingdates showed a significant difference on the plant height, plant stand at maturity and marketablebulb production. The highest fresh bulb yield (16.63 t ha-1) observed on the variety N-53. Similarly,August 15 transplanting date produced the highest bulb yield (15.31 t ha-1) among four transplantingdates. This novel technology for off-season onion bulb production through seedlings would be goodopportunity for increasing the income of many hill farmers which have no access to low land andirrigation facility during normal onion production season. The production of green tops in this periodis consumable and easily saleable in the local market. So farmers get extra income from thistechnology.Key words: Bulb yield; off-season onion; transplanting date; varietiesDOI: 10.3126/narj.v7i0.1862Nepal Agriculture Research Journal Vol.7 2006 pp.21-26